2008
DOI: 10.1080/13693780701591481
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis in Europe: Report on an epidemiological survey from the European Confederation of Medical Mycology Working Group

Abstract: The purpose of this survey was to systematically collect data on individuals with histoplasmosis in Europe over a 5-year period (from January 1995 to December 1999). This included information on where and how the infection was acquired, the patient's risk factors, the causative organism, how the infection was diagnosed and what therapy the patients received. Data were sent on a standardized survey form via a national convenor to the coordinator. During the survey, 118 cases were reported, with 62 patients havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 31 publications
8
85
0
8
Order By: Relevance
“…We have observed that this mycosis was more common in males (79.5%), especially males between the ages of 21 and 40 years with or without HIV/ AIDS. [17][18][19] Other studies have reported similar results; an epidemiological survey performed in European countries by the European Confederation of Medical Mycology Working Group found that 75% of histoplasmosis patients were males ages 21-40 years. 19 More recently, Arango and others 17 reported that, in a cohort of Colombian histoplasmosis cases, 77% were males, with a mean age of 38.4 years; an AIDSrelated condition was observed in 70.5% of these patients.…”
Section: Discussionsupporting
confidence: 62%
“…We have observed that this mycosis was more common in males (79.5%), especially males between the ages of 21 and 40 years with or without HIV/ AIDS. [17][18][19] Other studies have reported similar results; an epidemiological survey performed in European countries by the European Confederation of Medical Mycology Working Group found that 75% of histoplasmosis patients were males ages 21-40 years. 19 More recently, Arango and others 17 reported that, in a cohort of Colombian histoplasmosis cases, 77% were males, with a mean age of 38.4 years; an AIDSrelated condition was observed in 70.5% of these patients.…”
Section: Discussionsupporting
confidence: 62%
“…H. capsulatum is considered an endemic fungus of the Tennessee, Ohio, and Mississippi river basins occurring especially in soils contaminated with droppings of birds and bats. Moreover, an increasing number of autochthonous cases of histoplasmosis have been described in Europe (Ashbee et al, 2008).…”
Section: Fungimentioning
confidence: 99%
“…An epidemiologic survey in Europe showed that for at least 25% of patients, symptoms did not occur for at least five years after travel. 18 To the best of our knowledge, the present case is the most delayed diagnosis ever recorded for H. capsulatum var. duboisii, other than a case of H. capsulatum var.…”
mentioning
confidence: 99%